Aronia berry processing by spray drying : from byproduct to high quality functional powder - Vidović, Senka (Array, 2019)
The main aim of this study is to analyze the solid-liquid extraction followed by spray drying as a technological pathway for utilization of aronia fruit dust, a byproduct of filter tea factory. In the current study, ultrasound-assisted extraction was applied for the production of aronia liquid feed and maltodextrin was used as a carrier and encapsulating agent. In spray drying, the influence of inlet temperature and maltodextrin type and mass fraction on process efficiency and powder properties were observed. The physical and chemical properties of the obtained powders were characterized. It was determined that the powder produced using inlet temperature 140 °C and 40 % maltodextrin with dextrose equivalent (DE) 19.7 had the most desirable characteristics. It was observed that the increase in maltodextrin mass fraction decreases the powder moisture content, hygroscopicity and the content of bioactive compounds, but increases water solubility index and particle size. The increase in dextrose equivalent of maltodextrin increases the powder hygroscopicity and water solubility index, while the increase of inlet temperature causes a decrease in moisture content of aronia powders.